ETNOBOTANI TUMBUHAN BERKHASIAT OBAT SUKU DAYAK MAANYAN DESA TANIRAN KECAMATAN BENUA LIMA KABUPATEN BARITO TIMUR KALIMANTAN TENGAH - Tri Haryanto; Budi Sutiya; Yuniarti Yuniarti (Universitas Lambung Mangkurat, 2026)
Ethnobotanical studies aim to understand how individuals interact with their environment, both in traditional societies and today's industrialized societies. When talking about the interaction between humans and nature, the environment basically offers resources that must be used by its inhabitants to survive. The purpose of this study is to determine the types of plants and plant components used in traditional medicine. In addition, this study will examine how the Dayak Maanyan people process and use medicinal plants. The tools used in this study include a list of questions or questionnaires for the respondents involved as well as stationery and cameras. The main materials in this study are the plants used. Descriptive methodology was used in this research, along with in-depth interviews with selected resource persons, such as traditional healers and traditional leaders. The process undertaken to gather information and answer questions from respondents is outlined in this research technique. The conclusion of this study is that the number of medicinal plants utilized by the Dayak Manyan community is 30 types of plants. The part of the plant that is most often used by the Dayak Manyan community is the leaf, which is 44%, the root is 30%, the stem is 15% and the bark is 11%. There are 5 ways of processing plant parts to be used, namely by boiling, pounding, soaking, rubbing and eating.